Discovery and Structure-Activity Relationships of the Neoseptins: A New Class of Toll-like Receptor-4 (TLR4) Agonists - Morin, Matthew D.; Wang, Ying; Jones, Brian T.; Su, Lijing; Surakattula, Murali M. R. P.; Berger, Michael; Huang, Hua; Beutler, Elliot K.; Zhang, Hong; Beutler, Bruce; Boger, Dale L. (Journal of medicinal chemistry, 2016)
Herein, we report studies leading to the discovery of the neoseptins and a comprehensive examination of the structure activity relationships (SARs) of this new class of small-molecule mouse Toll-like receptor 4 (mTLR4) agonists. The compounds in this class, which emerged from screening an a-helix mimetic library, stimulate the immune response, act by a well-defined mechanism (mouse TLR4 agonist), are easy to produce and structurally manipulate, exhibit exquisite SARs, are nontoxic, and elicit improved and qualitatively different responses compared to lipopolysaccharide, even though they share the same receptor.